2011
DOI: 10.1186/1471-2180-11-141
|View full text |Cite
|
Sign up to set email alerts
|

The non-motile phenotype of Salmonella hha ydgT mutants is mediated through PefI-SrgD

Abstract: BackgroundTwo ancestral nucleoid-associated proteins called Hha and YdgT contribute to the negative regulation of several virulence-associated genes in Salmonella enterica serovar Typhimurium. Our previous work showed that Hha and YdgT proteins are required for negative regulation of Salmonella Pathogenicity Island-2 and that hha ydgT double mutants are attenuated for murine infection. Interestingly, hha ydgT mutant bacteria exhibited a non-motile phenotype suggesting that Hha and YdgT have a role in flagellar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 38 publications
2
8
1
Order By: Relevance
“…We also show that the PpefB promoter, but not the PpefA promoter, is silenced by Hha-YdgT and StpA, the paralog of H-NS, but these nucleoproteins affect pef operon transcription less than H-NS. The use of a double ΔhhaΔydgT mutant was necessary to obtain this phenotype, which is consistent with the already described redundancy of these proteins [25,36,47]. Concerning StpA, our results are the first demonstration of StpA gene silencing after bacterial growth in late stationary phase, i.e.…”
Section: Discussionsupporting
confidence: 90%
“…We also show that the PpefB promoter, but not the PpefA promoter, is silenced by Hha-YdgT and StpA, the paralog of H-NS, but these nucleoproteins affect pef operon transcription less than H-NS. The use of a double ΔhhaΔydgT mutant was necessary to obtain this phenotype, which is consistent with the already described redundancy of these proteins [25,36,47]. Concerning StpA, our results are the first demonstration of StpA gene silencing after bacterial growth in late stationary phase, i.e.…”
Section: Discussionsupporting
confidence: 90%
“…However, one of these three regulators, PefI, has already a known function as a negative regulator of the pef operon (Nicholson and Low, 2000). A putative role of SrgD as a transcriptional regulator of flagellar gene expression has also been suggested (Wozniak et al, 2009;Wallar et al, 2011) unlike the putative transcriptional regulator SrgC which has currently no described role.…”
Section: Discussionmentioning
confidence: 99%
“…According to the work of Wallar et al . () and Wozniak et al . (), SrgD could be involved in regulation of flagellar gene expression and motility.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…Also localized on the rck operon, srgD encodes a putative transcriptional regulator. Recently, it has been shown that SrgD acts in cooperation with PefI to induce a synergistic negative regulation of flagellar genes expression (Wozniak et al, 2009;Wallar et al, 2011). The remaining genes on the rck operon have unknown functions and encode a putative outer membrane protein, SrgB, and a putative transcriptional regulator, SrgC.…”
Section: Rck Regulationmentioning
confidence: 99%